The Application of Chicken Manure Fertilizer on the Growth and Yield of Shalot (Allium ascalonicum L.) Plants of the Tajuk Variety in a Floating System - Susilawati, Susilawati; Haqqi, Verza Dharma; Irmawati, Irmawati (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Susilawati, S., Haqqi, V. D., & Irmawati, I. (2024). The application of chicken manure fertilizer on the growth and yield of shalot (Allium ascalonicum L.) plants of the tajuk variety in a floating system. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 799–816). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Shallots are one of the plants that produce economically valuable bulbs that can becultivated conventionally or with a floating farming system. The purpose of this study was to determine the impact and best dosage of providing variations in chicken manure fertilizer with a floating system on the growth and yield of shallots (Allium ascalonicum L.) tajuk variety. This research was conducted at the Embung Faculty of Agriculture, Sriwijaya University with coordinates 003 ° 13'16